CHILD AND JUVENILE CRIMINALIZATION AND DRUGS SITUATION IN CHAPECÓ - SC: IN SEARCH OF PROPOSALS AND ALTERNATIVS (2019-2020) (Reflection and Critique Law Magazine, 2023)
This research is a continuation of a study initiated in 2017 under the coordination of Dr. AUTORA, adopting as a field of analysis the relationship between drug use, the psychosocial identity of children and adolescents in the city of Chapecó, as well as reflex public policies. At that time, it was identified that the presence of vulnerability in the context of the study is relatively low in relation to the total resident population, however, the absence of effective public policies increases the imagery of the “public enemy”. It was proposed, then, as an alternative to improve the problem situation, school monitoring, citizen development and monitoring of weaknesses. In this continuation, the range of attention was opened to the environmental aspect and historical formation of the communities commonly affected and how this implies in the recognition of social identity with the criminal world, the formation of territorialities and in the processes of exclusion. The violent dynamics that we currently follow are a direct reflection of the contexts of exclusion and identification.